2013
DOI: 10.1016/j.blre.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Current therapy of myelodysplastic syndromes

Abstract: After being a neglected and poorly-understood disorder for many years, there has been a recent explosion of data regarding the complex pathogenesis of myelodysplastic syndromes (MDS). On the therapeutic front, the approval of azacitidine, decitabine, and lenalidomide in the last decade was a major breakthrough. Nonetheless, the responses to these agents are limited and most patients progress within 2 years. Allogeneic stem cell transplantation remains the only potentially curative therapy, but it is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 219 publications
0
90
1
Order By: Relevance
“…TD anemia leading to secondary IO has been associated with adverse clinical outcomes and adverse effects on survival in patients with MDS [3][4][5][6]. Although no randomized prospective data examining the impact of ICT on survival in MDS have been reported to date, iron chelation therapy (ICT) is commonly prescribed to MDS patients with TD anemia, especially patients with lowerrisk (LR) MDS [7,8]. We have recently shown that ICT use in MDS has increased since the US FDA approval of the first oral chelator deferasirox (DFX) in 2005 [9].…”
Section: Introductionmentioning
confidence: 99%
“…TD anemia leading to secondary IO has been associated with adverse clinical outcomes and adverse effects on survival in patients with MDS [3][4][5][6]. Although no randomized prospective data examining the impact of ICT on survival in MDS have been reported to date, iron chelation therapy (ICT) is commonly prescribed to MDS patients with TD anemia, especially patients with lowerrisk (LR) MDS [7,8]. We have recently shown that ICT use in MDS has increased since the US FDA approval of the first oral chelator deferasirox (DFX) in 2005 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Those with higher risk MDS (intermediate-2, high) have a median survival of <1 year, whereas those with lower risk MDS (intermediate-1, low) have a median survival of 3-8 years [3]. Prediction of outcomes is important in management as this impacts risk/benefit estimations for initiation of treatment, including hypomethylating agents (HMAs) and allogeneic hematopoietic cell transplantation (AlloHCT) [4]. Although HMAs improved outcomes for patients with higher risk MDS, not all patients benefit from this therapy and no reliable methods have been discovered to predict differential likelihood of benefit from HMAs.…”
mentioning
confidence: 99%
“…Higher-risk MDS represents a significant therapeutic treatment challenge for any current chemotherapeutics because of poor responses to combination chemotherapy and shorter survival (25). Previous large studies using various induction regimens containing AraC in various combinations with idarubicin, fludarabine, topotecan, and cyclophosphamide demonstrated CR rates of ~40-60% for higher-risk MDS, median OS rate 10.4-13 months, and treatment-related early death 10-20% (2,3,26,27).…”
Section: Discussionmentioning
confidence: 99%